(untitled) - Kilianova, Katarina (Doprava a spoje, 2012)
The article specified many factors which have influence to costs. Try to specify these factors are necessary in case of pricing in public passenger transport. Since The Regulation (EC) No 1370/2007 of the European Parliament and of the Council of 23 October 2007 on public passenger transport services by rail and by road has valid, it is hard to estimate economically eligible costs. Because of the fact, the article deals with factors which affecting to costs. With the help of correlation is possible to determine the degree of influence and choose the factor with the biggest influence.